2007
DOI: 10.1101/gad.1588407
|View full text |Cite
|
Sign up to set email alerts
|

Lineage tracing demonstrates the venous origin of the mammalian lymphatic vasculature

Abstract: The origin of the mammalian lymphatic vasculature has been debated for more than 100 years. Whether lymphatic endothelial cells have a single or dual, venous or mesenchymal origin remains controversial. To resolve this debate, we performed Cre/loxP-based lineage-tracing studies using mouse strains expressing Cre recombinase under the control of the Tie2, Runx1, or Prox1 promoter elements. These studies, together with the analysis of Runx1-mutant embryos lacking definitive hematopoiesis, conclusively determined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

26
552
3
6

Year Published

2008
2008
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 494 publications
(594 citation statements)
references
References 44 publications
26
552
3
6
Order By: Relevance
“…To assess the specificity of Pdgfrb‐Cre mediated targeting of LECs of different origins, we analysed Cre mediated recombination in the cardinal vein that provides a source of the first venous derived LECs, the peripheral longitudinal lymphatic vessel and the primordial thoracic duct, that are also referred to as the jugular lymph sacs (JLS) (Hagerling et al, 2013; Srinivasan et al, 2007; Yang et al, 2012). Immunofluorescence analysis of E13.5 Pdgfrb‐Cre ; R26‐mTmG embryos showed the expected GFP + perivascular cells (Foo et al, 2006) (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To assess the specificity of Pdgfrb‐Cre mediated targeting of LECs of different origins, we analysed Cre mediated recombination in the cardinal vein that provides a source of the first venous derived LECs, the peripheral longitudinal lymphatic vessel and the primordial thoracic duct, that are also referred to as the jugular lymph sacs (JLS) (Hagerling et al, 2013; Srinivasan et al, 2007; Yang et al, 2012). Immunofluorescence analysis of E13.5 Pdgfrb‐Cre ; R26‐mTmG embryos showed the expected GFP + perivascular cells (Foo et al, 2006) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…These observations were made in the context of the startling discovery that LECs in the heart (Klotz et al ., 2015), mesentery (Stanczuk et al . 2015), and skin (Martinez‐Corral et al ., 2015), not only develop through lymphangiogenic sprouting from a venous blood vascular source, which has previously been the only known mechanism for lymphatic vessel formation in mammals (Srinivasan et al ., 2007), but also through the assembly of nonvenous derived LEC progenitors.…”
Section: Introductionmentioning
confidence: 99%
“…An alternative, "centripetal" theory, suggests that LECs are derived from mesenchymal progenitor cells, which, nowadays, are called lymphangioblasts (Huntington and Mc Clure 1910). Several recent studies in genetically engineered mouse models (Srinivasan et al 2007;Wigle et al 2002;Wigle and Oliver 1999) and in vivo imaging of developing lymphatic vasculature in zebraWsh (Yaniv et al 2006) provide strong support for the venous origin of lymphatic vessels. Lineage tracing experiments demonstrate that LECs originating in embryonic veins are the main source for the developing lymphatic vasculature; they have also identiWed some of the molecular determinants that control the step-wise process of lymphatic competence, commitment, diVerentiation and maturation (reviewed in Adams and Alitalo 2007;Karpanen and Alitalo 2008;Oliver 2004).…”
Section: Embryonic Development Conceptsmentioning
confidence: 99%
“…In murine embryos, scattered mesenchymal cells, which coexpress leukocyte (CD45) and lymphatic endothelial markers (LYVE-1, PROX1), were detected in the regions of new lymphatic vessel growth; and it was suggested that the triple positive cells (LYVE-1 + , PROX1 + , F4/80 + ) with characteristics of LECs and macrophages may integrate into lymphatic vessels (Buttler et al 2006(Buttler et al , 2008a. The functional role of such cells remains unclear, as formation of lymph sacs is not aVected in Runx1 ¡/¡ mice, which have defective hematopoiesis, and lineage tracing studies failed to demonstrate contribution of hematopoietic cells to lymphatic endothelium up to the embryonic day E16.5 (Buttler et al 2008b;Srinivasan et al 2007). A possibility remains that hematopoietic cells contribute to developmental lymphangiogenesis in a noncell autonomous manner, as described previously for angiogenesis .…”
Section: Embryonic Development Conceptsmentioning
confidence: 99%
“…Un article récent utilisant un système de traçage génétique complété par des knock-in spécifiques plaide en faveur de cette origine [10]. Les auteurs ont créé une souche de souris portant le gène codant pour la recombinase CRE fusionnée au domaine de liaison muté du récep-teur des oestrogènes (CRE-ER T2 ), le tout inséré en phase dans le locus de marqueurs moléculaires spécifi-ques des vaisseaux lymphatiques qui, couplée à des approches de transgenèse, a permis de lever une partie du voile sur l'origine des vaisseaux lymphatiques.…”
Section: L'hypothèse De Florence Sabin Sur L'origine Du Réseau Lymphaunclassified